State Misallocation and Housing Prices: Theory and Evidence from China - Wang, Shing-Yi (American Economic Review, 2011)
This paper examines the equilibrium price effects of the privatization of housing assets that were previously owned and allocated by the state. I develop a theoretical framework that shows that privatization can have ambiguous effects on prices in the private market, and that the degree of misallocation of the assets prior to privatization determines the subsequent price effects. I test the predictions of the model using a large-scale housing reform in China. The results suggest that the removal of price distortions allowed households to increase their consumption of housing and led to an increase in equilibrium housing prices. (JEL L33, O18, P25, R31, R38)